2002
DOI: 10.1046/j.1469-0691.2002.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal toxic shock syndrome: a description of 14 cases from North Yorkshire, UK

Abstract: There has been a dramatic increase in the number of detected cases of streptococcal TSS over the 14 years since the first case was recognized here. There was a wide range of invasive forms of infection, a high fatality rate even in fit young adults, and a rapid course from onset to death. There was a high association of TSS with aggressive streptococcal infection producing local tissue necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 41 publications
3
51
0
2
Order By: Relevance
“…), the causative bacteria in six cases were identified as S. dysgalactiae subsp. equisimilis (2,27,38) and S. equisimilis (24,45), which was renamed as S. dysgalactiae subsp. equisimilis according to the latest classification (47,48), while other reports did not identify the species of the causative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), the causative bacteria in six cases were identified as S. dysgalactiae subsp. equisimilis (2,27,38) and S. equisimilis (24,45), which was renamed as S. dysgalactiae subsp. equisimilis according to the latest classification (47,48), while other reports did not identify the species of the causative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Since then the number of patients of this serious infectious disease has been increasing in North America, Europe, and other parts of the world (2,10,18,21,34). The Working Group on Severe Streptococcal Infections suggested a case definition of streptococcal toxic shock syndrome (STSS) and necrotizing fasciitis (52).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…equisimilis strains having group A antigen rather than group C or G antigen have also been reported (Bert & Lambert-Zechovsky, 1997;Brandt et al, 1999;Katsukawa et al, 2002). Many recent studies have reported that this organism causes invasive and systemic streptococcal infections like GAS (Natoli et al, 1996;Wagner et al, 1996; Hirose et al, 1997; Kugi et al, 1998;Barnham et al, 2002;Cohen-Poradosu et al, 2004;Hashikawa et al, 2004). The organism has also been reported to cause a wide variety of human infections such as pharyngitis, cellulitis, sepsis, meningitis and endocarditis (Woo et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…20 Both leukocytosis and leukopenia have been described in NF, the latter possibly due to depletion of circulating white cells sequestered in peripheral tissues. 1,12 Isolation of Streptococcus spp. from either a sterile or a nonsterile site of the body coupled with 2 or more clinical signs is required to confirm the diagnosis.…”
mentioning
confidence: 99%